1989
DOI: 10.1088/0022-3727/22/8/011
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of streamers

Abstract: Measurements have been carried out with a fast photomultiplier on a unique streamer in a point-plane gap in atmospheric air (positive direct tension applied to the point). Three different kinds of experiments have been done: streamer heads statistics as a function of applied voltage; streamer propagation in weak applied field; and streamer head characteristic dimension for which the value obtained is about 170 mu m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 4 publications
6
14
0
1
Order By: Relevance
“…After the Abel inversion, we found that the diameter of the streamer is ~155 μm. This agrees with the results of Gibert, et al [15] or Van Veldhuizen, et al [16] who also applied optical emission measurement. However, it is much larger than the streamer diameter 40 μm measured by Bastien, et al [17] who measured it from the broadening of H lines that is related to the current density, so it may be closer to real plasma "electrical" diameter.…”
Section: Fig 5 Radial Intensity Profiles Of Single Streamer and Spasupporting
confidence: 92%
“…After the Abel inversion, we found that the diameter of the streamer is ~155 μm. This agrees with the results of Gibert, et al [15] or Van Veldhuizen, et al [16] who also applied optical emission measurement. However, it is much larger than the streamer diameter 40 μm measured by Bastien, et al [17] who measured it from the broadening of H lines that is related to the current density, so it may be closer to real plasma "electrical" diameter.…”
Section: Fig 5 Radial Intensity Profiles Of Single Streamer and Spasupporting
confidence: 92%
“…The optical microdischarge average diameter obtained from this picture is around 200 µm. Although this value is in the upper limit of the streamer diameter estimates generally published in the literature, it is in good agreement with values reported in refs 17, 37. The picture also indicates that the streamer bridges the electrode gap in less than 50 ns (the exposure time corresponding to this picture), a value that represents an upper limit of the streamer phase duration.…”
Section: Resultssupporting
confidence: 91%
“…Gibert and Bastien [19] reported the value 0.017 cm for the measured optical streamer diameter in air. As discussed above, l ρ defines the optical radius of the streamer.…”
Section: Discussionmentioning
confidence: 93%
“…In our notations the Penney and Hummert expression for S ph2 [15] is S ph2 = S i1 ψ air (pr θ )hp dθ (19) where ψ air (pr θ ) is the absorption function, tabulated in [15]. Equating (19) and (18) yields the relation between f and ψ air…”
Section: Comparison With Penney and Hummert Datamentioning
confidence: 99%
See 1 more Smart Citation